Pragmatic development in Peruvian children: Modality and lexical development between 8 and 15 months of age - (:unkn) unknown (John Benjamins Publishing Company, 2024)
This study examines how 8- to 15-month-old Peruvian children (N = 18) express pragmatic functions in terms of the modality and referential-specificity level of each communicative behaviour. Results show that pragmatic functions were expressed mainly ...
Keywords: Desarrollo pragmático; Lenguaje infantil